Sea Urchins Play an Increasingly Important Role for Coral Resilience Across Reefs in Taiwan - Dang, Viet D. H.; Cheung, Pak-Yin; Fong, Chia-Ling; Mulla, Aziz J.; Shiu, Jia-Ho; Lin, Che-Hung; Nozawa, Yoko (Frontiers in Marine Science, 2020)
Herbivores are an important functional group that control algae, creates new space, and promotes recruitment for coral recovery. However, along many coral reefs, overfishing has greatly decreased the density of herbivores, especially fishes and gastropods, impairing coral resilience. On such overfished reefs, remnant herbivores that are not target species of local fisheries, e.g., sea urchins, are expected to play an increasingly important role, yet few studies, with the exception of those in the Caribbean and Kenya, have examined non-fish herbivores in relation to coral resilience. Here, we conducted field surveys at 30 sites along 3 coral reefs in Taiwan between 2016 and 2017, to examine the relative importance of 6 key factors for coral resilience: herbivore abundance (fishes, gastropods, sea urchins), coral cover, macroalgal cover, habitat complexity, water depth, and wave exposure. The density of juvenile coral was used as a proxy of coral resilience. Diadematid sea urchins (Echinothrix spp. and Diadema spp.) were observed to dominate the majority of sites (19 of 30 sites) and multivariable regression models showed sea urchin density as the best positive predictor of coral juvenile density. The results elucidated the increasing role diadematid sea urchins play as remnant herbivores on overfished coral reefs in Taiwan. Given that overfishing is a widespread issue, this phenomenon may be occurring globally. More studies are needed to examine the role of remnant, but often ignored, sea urchin herbivory on coral resilience. Reef managers should consider incorporating locally remnant herbivores into management strategies.